Pengaruh Flashcard Terhadap Pengetahuan Gizi Dan Kecukupan Asupan Energi Pada Anak Remaja di Sekolah Lanjut Tingkat Pertama (SLTP) Kota Pontianak - Dahliansyah, Dahliansyah; Karunia, Wiga; Gambir, Jurianto (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2024)
Background: Adolescents are the next generation of the nation in the future, adolescents make up the majority of the world's population of 1.2 billion young people, nearly 90% of whom are in developing countries. The causes of nutritional problems in adolescence are direct factors such as food intake and infectious diseases. In addition, low knowledge of nutrition can lead to nutritional problems in adolescents, especially anemia and chronic undernutrition. Knowledge is the understanding of information about a particular topic, as well as the ability to receive, retain and use information. One of the media that can increase knowledge is flashcards, as one of the developments of visual media in the form of alternating cards that will be carried out by playing. Aim this research is to determine the effect of nutrition education through flashcards media on nutritional knowledge and adequacy of energy intake in Adolescent Children in Pontianak City Junior High School (SLTP). Methods: This study used quasy-experiment with pretest-posttest control group design. The subjects of this study were adolescents of MTsN 1 and SMPN 12 Pontianak. The population in this study were all adolescent IX students totaling 189 people at MTsN 1 Pontianak, the number of samples was 44 people consisting of 22 experimental samples and 22 control samples, which were selected using purposive sampling method. Data collection techniques with direct interviews. The treatment was conducted for 8 meetings within 1 month. Results: The results of the average nutritional knowledge score between before and after being given nutrition education in both groups showed a significant increase, namely p-value <0.05. While the average result of energy intake between before and after being given nutrition education in both groups is 0.05 which means there is no significant increase. Conclusion: Providing nutrition education using flashcards can improve nutritional knowledge.